2012
DOI: 10.1111/j.1756-8765.2012.01223.x
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Learning and Acquisition of Music

Abstract: Implicit learning is a core process for the acquisition of a complex, rule-based environment from mere interaction, such as motor action, skill acquisition, or language. A body of evidence suggests that implicit knowledge governs music acquisition and perception in nonmusicians and musicians, and that both expert and nonexpert participants acquire complex melodic, harmonic, and other features from mere exposure. While current findings and computational modeling largely support the learning of chunks, some resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
102
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(109 citation statements)
references
References 186 publications
(217 reference statements)
4
102
0
3
Order By: Relevance
“…Conclusiveness ratings did not differ between conditions when participants indicated that they based their rating on intuition or guessing. This finding is in agreement with explicit judgment knowledge found in musical-learning studies (39). Explicit judgment knowledge does not necessarily imply that individuals had explicit structural knowledge (i.e., that they actually knew the rule), but that they were aware of knowledge that guided their responses (35).…”
Section: Discussionsupporting
confidence: 81%
“…Conclusiveness ratings did not differ between conditions when participants indicated that they based their rating on intuition or guessing. This finding is in agreement with explicit judgment knowledge found in musical-learning studies (39). Explicit judgment knowledge does not necessarily imply that individuals had explicit structural knowledge (i.e., that they actually knew the rule), but that they were aware of knowledge that guided their responses (35).…”
Section: Discussionsupporting
confidence: 81%
“…Two other systems that are particularly likely to play a role in both domains are implicit learning and working memory. Implicit learning plays an important role in the acquisition of complex structural knowledge, both in language (e.g., Saffran, Aslin, & Newport, 1996;see Kuhl, 2004, for a review) and in music (e.g., Ettlinger, Margulis, & Wong, 2011;Loui, Wu, Wessel, & Knight, 2009;Loui, Wessel, & Husdon Kam, 2010;Loui, 2012;Rohrmeier & Rebuschat, 2012). Support for shared reliance on implicit learning mechanisms comes from the finding that musical training (which presumably places additional demands on implicit learning mechanisms) leads to better implicit learning of both musical and linguistic structure (Francois & Schön, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we consider "syntax" generally as the knowledge of regularities that 50 control the integration of smaller units into larger musical phrases (Swain, 1995) and thereby 51 support predictions. It is well established that tacit knowledge about structural regularities of 52 music 1) is acquired implicitly (Loui et al, 2009;Rohrmeier and Rebuschat, 2012;Tillmann 53 et al, 2000), 2) largely shapes our musical competence across different musical systems and 54 cultures (Eerola et al, 2006;Lartillot and Ayari, 2011), and 3) enables listeners to cognitively 55 link current auditory items to past events and to generate predictions on forthcoming events 56 (Patel, 2003;Tillmann, 2012). In the present study we will focus on harmonic regularities and 57 investigate how they govern predictions during (auditory) music perception and (silent) 58 musical actions.…”
mentioning
confidence: 99%